A DESCRIPTIVE STUDY ON CONSUMER ATTITUDE TOWARDS GREEN ADVERTISING INFLUENCING PURCHASE INTENT OF SUSTAINABLE FMCGS - Jonker, Jacolene (The IIE, 2020)
A heightened level of consumer consciousness, with regards to consumption habits, have led to greater sustainable purchase intents. With sustainable purchases on the rise, green advertising sets out to inform consumers about sustainable products. The objective hereof is to influence consumer preference of sustainable products. Unknown to the topic of green advertising is how consumer attitude comes into effect when considering the matter of purchase intent. In line with this, the study aims to address the matter of how consumer attitude towards green advertising influences the purchase intent of sustainable FMCGs, through following a positivistic research approach. This study is of a quantitative, cross-sectional, nature. The Theory of Planned Behaviour created the foundation from which this study was conducted, as attitude is a key factor hereof. The reviewed literature conceded factors related to attitude, green advertising and purchase intent. The study followed a positivistic approach, thus quantitative data was evaluated by means of thematically grouping statistical findings. This was with the purpose to measure the extent to which attitude towards green advertising influences purchase intent. From a sample of 24 responses, a seemingly positive attitude towards green advertising was displayed. This study contributes to understanding attitudinal factors, in relation to green adverting, influencing purchase intent of sustainable FMCGs.
Keywords: Green advertising; Sustainability; Consumer behaviour; Consumer purchase intent; Fast-Moving Consumer Goods; FMCGs; Environmental concern